Analysis of Cervical Cancer Screening Behavior in Women of Childbearing Age from the Perspective of the Health Belief Model - Yunita Kristina; Hadija; Sumarah; Fitri Khairani (CV. Get Press Indonesia, 2026)
Cervical cancer remains a major public health problem, particularly in developing countries where low screening coverage contributes to high morbidity and mortality among women. This study aimed to analyze cervical cancer screening behavior among women of reproductive age based on the Health Belief Model (HBM). An analytical observational study with a cross-sectional design was conducted in Padang City from January to February 2026. A total of 422 women of reproductive age were selected through simple random sampling. Cervical cancer screening was defined as having undergone at least one screening method, including Visual Inspection with Acetic Acid (VIA), Pap smear, or Human Papillomavirus (HPV) testing. Data were collected using a validated questionnaire and analyzed using Chi-square and logistic regression tests. Only 39.8% of respondents had ever undergone screening (95% CI: 35.1–44.5%). Significant associations were found between screening behavior and perceived susceptibility (p=0.012), perceived benefits (p=0.001), perceived barriers (p<0.001), cues to action (p<0.001), and self-efficacy (p<0.001), while perceived severity was not significantly associated (p=0.087). Multivariable analysis showed that perceived barriers and self-efficacy remained independently associated with screening behavior. These findings suggest that reducing perceived barriers and strengthening self-efficacy may improve cervical cancer screening uptake among women.